Bioremediation of crude oil by white rot fungi polyporus sp. S133 - Kristanti, Risky Ayu (Korean Society for Microbiolog and Biotechnology, 2011)
The bioremediation potential of crude oil by Polyporus sp. S133 pre-grown in wood meal was investigated in two separate experiment trials; liquid medium and soil. The effect of three nutrients (glucose, polypeptone, and wood meal), oxygen flow, and some absorbent on the efficiency of the process was also evaluated. Degradation of crude oil in soil was significantly increased with an addition of oxygen flow and some absorbent (kapok and pulp). The highest degradation rate of crude oil was 93% in the soil with an addition of 10% kapok. The present study clearly demonstrates that, if suitably developed, Polyporus sp. S133 could be used to remediate soil contaminated with crude oil.